Convergence of Per Capita Output Levels Across Regions of Bangladesh, 1982-97 - Hossain, Akhtar (Washington, D.C. : International Monetary Fund, 2000)
This paper has examined the phenomenon of convergence of per capita output levels across regions of Bangladesh during 1982-97. The main finding is that most of the regions of Bangladesh experienced strong convergence of per capita output levels during 1982-91. There are two other findings within the domain of convergence. First, a few poorer regions of the country did not demonstrate any output convergence for the full or part of the sample period. Second, no evidence has been found for regional convergence of per capita output levels during 1991-97 that coincided with opening up the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet